EVALUASI PENERAPAN PENDIDIKAN KESETARAAN DI PONDOK PESANTREN SALAFIYAH TAHFIDZUL QUR’AN AHLUS SHUFFAH BALIKPAPAN - Aristya, Septian; Zamroni, Zamroni (STAI Sangatta Kutai Timur, 2024)
This research aims to analyze the concept of evaluating the application of equality education and the results of the evaluation of the application of equality education at the Salafiyah Tahfidzul Qur'an Ahlus Shuffah Balikpapan Islamic Boarding School. The method used in this research is a qualitative research method with a context, input, process, and product (CIPP) analysis model. The research results show that the results of the context analysis evaluation support the implementation of equality programs, but there are still limitations. Evaluation of input analysis in the form of students coming from outside the region, which is considered diverse, the availability of tutors, infrastructure is sufficient, and textbooks are still limited to teacher handbooks. Evaluation of process analysis where the availability of various activities is an advantage at PKPPS Tahfidzul Qur'an Ahlus Shuffah. Learning has maximized the use of existing infrastructure. The product analysis evaluation is reflected in the graduate data from Pondok Tahfidzul Qur'an Ahlus Shuffah Balikpapan, which has not yet been updated, but from the information obtained, 100% of the students were able to complete the program well. As for the output of the graduates, they have worked, teach, and some have even become lecturers at universities. It is hoped that this evaluation can provide valuable input for the development of equality programs among Islamic boarding schools, especially in East Kalimantan.